Nano‐antennae assisted emission of extreme ultraviolet radiation. Issue 3 (10th March 2014) - Pfullmann, Nils; Noack, Monika; Cardoso de Andrade, José; Rausch, Stefan; Nagy, Tamas; Reinhardt, Carsten; Knittel, Vanessa; Bratschitsch, Rudolf; Leitenstorfer, Alfred; Akemeier, Dieter; Hütten, Andreas; Kovacev, Milutin; et al.
<x xml:space="preserve">Abstract</x> High‐order harmonic generation in xenon with oscillator repetition rates is studied. The necessary intensity is reached via plasmonic field enhancement at nanostructured arrays of bow‐tie gold antennae. The theoretical analysis focuses on the thermal properties and the damage threshold of the bow‐tie antennae. On the experimental side the number of contributing atoms is determined and optimized. Extreme ultraviolet radiation is successfully observed with photon fluxes almost an order of magnitude larger than previously reported.